Islamic Legal Analysis of Bank Interest Allocation on Social Fund: A Case Study of Small Credit Bank (BPR) NBP 21 Panyabungan City - Putra, Dedisyah; Harahap, Sumper Mulia; Edi, Sabrun (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The aim of this study was to determine the position of Ash Ziqri savings in conventional bank from Islamic law perspective using empirical legal study methods. This was achieved by collecting data through document study, observation, and interviews. The results showed that Ash Ziqri savings with bank interest withdrawal rate of 5% were considered usury from Islamic legal perspective. Savings were also considered gharar even though the payments were not intended for customers or bank but channeled through charitable activities such as the construction of mosques and the provision of compensation for orphans and the poor. Therefore, the public was encouraged to conduct social charity activities through zakat, infaq, and sadaqah without mixing the process with activities prohibited by Islam.